Enhancement of human adipose-derived stem cell spheroid differentiation in an in situ enzyme-crosslinked gelatin hydrogel. Issue 7 (18th January 2019) - Tsai, Ching-Cheng; Hong, Yu-Jun; Lee, Randall J.; Cheng, Nai-Chen; Yu, Jiashing
Abstract : Standardized human adipose-derived stem cell spheroids can be harvested abundantly and the differentiation capability of cell spheroids performed well in the enzyme-crosslinked gelatin hydrogel. Abstract : Human adipose-derived stem cells (hASCs) can differentiate into multiple lineages and be harvested abundantly. However, the expression of pluripotency markers, which is important for the renewal and differentiation capabilities of hASCs, decreases during monolayer culture. Increasing evidence has proven that cells aggregated to form cell spheroids in 3D cell cultures better mimic the in vivo microenvironment and can enhance the expression of stemness markers. In this study, uniform hASC spheroids were formed by seeding cells in agarose microwell plates, and the size of the spheroids could be adjusted. Most importantly, the stemness expression of the spheroids increased significantly. Additionally, we utilized microbial transglutaminase (mTG), which is an enzyme that exhibits highly specific activity over a wide range of temperature and pH, to crosslink gelatin. The enzymatic crosslinking reaction is milder than physical and chemical methods, which may lead to cell death. The properties of the gelatin/mTG hydrogel were evaluated in detail. In addition, the spheroids were encapsulated in the 3D hydrogel successfully. The results showed that the hydrogel has low toxicity to the cells, which significantly proliferated in the 3D hydrogel. Moreover, the analysis of the differentiation potential indicated that the cell spheroids in the 3D hydrogel exhibited good activity, especially adipogenesis and chondrogenesis, compared to the cell suspension group. Furthermore, the in vivo data confirmed the excellent injectability and biocompatibility of the 3D hydrogel.